2009
DOI: 10.1089/pho.2007.2206
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiographic Investigation of the Adjunctive Effects of a Low-Power He-Ne Laser in the Treatment of Moderate to Advanced Periodontal Disease: A Pilot Study

Abstract: Within the limits of this pilot study, the use of the low-power He-Ne laser as an adjunct to non-surgical periodontal therapy in patients with moderate to advanced chronic periodontitis did not seem to provide additional clinical benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 40 publications
1
55
3
1
Order By: Relevance
“…In a case-control study, LLLT add on therapy improved not significantly oral health in terms of PD reduction, but it resulted in a significantly higher reduction in bleeding scores compared to non surgical treatment alone. 24 Moreover, in a split-mouth study Lai et al 25 The present study has, in our opinion, some limitations. First, the small sample size.…”
Section: Discussionmentioning
confidence: 66%
“…In a case-control study, LLLT add on therapy improved not significantly oral health in terms of PD reduction, but it resulted in a significantly higher reduction in bleeding scores compared to non surgical treatment alone. 24 Moreover, in a split-mouth study Lai et al 25 The present study has, in our opinion, some limitations. First, the small sample size.…”
Section: Discussionmentioning
confidence: 66%
“…No papers on Flower Therapy were included because we found no RCT about this CIP. The use of CIP was predominantly associated with the treatment of periodontal disease (ANDERSEN et al, 2007;ANGELOV et al, 2009;CARUSO et al, 2008;DE ANDRADE et al, 2008;DE OLIVEIRA et al, 2007DERDILOPOULOU et al, 2007;GEORGE et al, 2009;JAIN et al, 2008;KAMMA et al, 2009;KELBAUNSKIENE et al, 2007;LAI et al, 2009;LOPES et al, 2010;MOMMOLO et al, 2008;MUÑOZ et al, 2001;OZCELIK et al, 2008;POLASNKSY et al, 2009;QADRI et al, 2005;RASSAMEEMASMAUNG et al, 2007;RIEGER et al, 2002;RODRIGUES et al, 2009;SASTRAVAHA et al, 2003;SCHWARZ et al, 2001;SIGUSCH et al, 2010;TING et al, 2007), different types of orofacial pain FACCO et al, 2008;GODDARD et al, 2002;KATSOULIS et al, 2001KATSOULIS et al, , 2010KITADE;OHYABU, 2000;MAZZETTO et al, 2007;MICHALEK-SAUBERER et al 2007;MOUSAVI et al, 2009a and b;POHODENKO-CHUDAKOVA, 2005;SCHMID-SCHWAP et al, 2006;SIMMA et al, 2009;SMITH et al, 2007;TORTAMANO et al, 2009;VENÂNCIO et al, 2005) and reduction in biofilm formation (AL TEEN et al, 2006;…”
Section: Resultsmentioning
confidence: 99%
“…The 'split mouth design' was used in some researches analyzed in this review (ASSAF et al, 2007;CARUSO et al, 2008;DERDILOPOULOU et al, 2007;DE OLIVEIRA et al, 2007;KAMMA et al, 2009;KELBAUSKIENE;MACIULSKIENE, 2007;LAI et al, 2009;LOPES et al, 2010;MUMMOLO et al, 2008;OZCELIK et al, 2008;PEREIRA et al, 2010;QADRI e tal., 2005;RODRIGUES et al, 2009;SCHWARZ et al, 2001;ZEZELL et al, 2009). We detected the 'split mouth design' as complicating factor to planning, conducting and analyzing the result of RCTs, especially in studies evaluating the use of CIP.…”
Section: Resultsmentioning
confidence: 99%
“…12 Contrary to our findings, Lai et al suggested that low-power laser did not result in any additional clinical benefit. 13 This might be a result of their application power density being low (2.83 mW/cm 2 ) and having limited application sites. The use of different kinds of lasers, doses, and duration preclude a comparison of these studies with our study.…”
Section: Discussionmentioning
confidence: 99%